2015
DOI: 10.3390/rs70606576
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adaptive Gradient-Based Thresholding Method for Coal Fire Detection Using ASTER Thermal Infrared Data, Part I: Methodology and Decadal Change Detection

Abstract: Coal fires that are induced by natural spontaneous combustion or result from human activities occurring on the surface and in underground coal seams destroy coal resources and cause serious environmental degradation. Thermal infrared image data, which directly measure surface temperature, can be an important tool to map coal fires over large areas. As the first of two parts introducing our coal fire detection method, this paper proposes a self-adaptive threshold-based approach for coal fire detection using AST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The use of ASTER TIR scenes acquired during different seasons precludes the use of a fixed threshold for segmenting temperature images. We previously addressed this limitation and proposed a method (SAGBT) that can be applied to multiple ASTER TIR scenes in a consistent and uniform way [8]. SAGBT defines coal fire areas as regions with temperature anomalies bounded by sharp decreases in LST, from central high temperature anomalies to low background temperature.…”
Section: Coal Fire Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of ASTER TIR scenes acquired during different seasons precludes the use of a fixed threshold for segmenting temperature images. We previously addressed this limitation and proposed a method (SAGBT) that can be applied to multiple ASTER TIR scenes in a consistent and uniform way [8]. SAGBT defines coal fire areas as regions with temperature anomalies bounded by sharp decreases in LST, from central high temperature anomalies to low background temperature.…”
Section: Coal Fire Detectionmentioning
confidence: 99%
“…We observed that these extreme gradient lines maintain topological properties and connect high gradient pixels in the gradient image and surrounding high temperature areas in the temperature image. Masked within the fire risk area that is closed by the outer boundaries of the coal-bearing strata, an intermediate threshold was retrieved by reading an average temperature along the thinned extremely high gradient lines from the potential high temperature image (high temperature image showed in Figure 3a) [8]. In the fine-tuning process, the final threshold was selected as the mean value of multiple intermediate thresholds generated by eleven line sequences resulting from thinned extreme gradient images.…”
Section: Coal Fire Detectionmentioning
confidence: 99%
See 3 more Smart Citations